PENYELESAIAN PERKARA KECELAKAAN LALU LINTAS DENGAN PELAKU DIBAWAH UMUR - Joshua Evandeo Irawan; Sari Mandiana; Agustin Widjiastuti (Universitas Merdeka Madiun, 2020)
Traffic accident often happens and involved underage child as driver of the vehicle and might lead to fatal consequences, such as the death casualities. In Indonesia, it is stipulated in Act No. 22 Year 2009 concerning Traffic and Road Transportation. The result shows that M’s illegal underage driving caused the death of K. Thus, M and his family are obliged to give compensation to the K’s family as stipulated in of Act No. 22 Year 2009 throughout Juvenile Justice System as the case procedur using Diversion case is stipulated in Act No. 11 Year 2012 regarding Juvenile Justice System